2019
DOI: 10.1590/1676-0611-bn-2018-0664
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of mating behavior and antennal sensilla in Anomala inconstans Burmeister, 1844 (Coleoptera: Scarabaeidae: Rutelinae)

Abstract: When suitable, adults of Scarabaeidae usually form swarms to find food and breeding sites. The steps of mating behavior can be mediated by chemical communication, and antennal sensilla are released volatiles detection structures, as sexual pheromones. In present work the mating behavior and the antennal sensilla of Anomala inconstans Burmeister, 1844 are described. The study was conducted at the Universidade Estadual de Mato Grosso do Sul, Cassilândia, Brazil from March 2015 to December 2017. Adults were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…This process is quite similar to that observed in other Cyclocephala species such as C. melanocephala, C. testaceipennis, and C. verticalis (Rodrigues et al 2014, Barbosa & Rodrigues 2016. Female selection in Scarabaeidae may be related to the recognition of male sexual maturity as in Canthon cyanellus cyanellus (LeConte, 1859) (Fávila 1988) and C. verticalis (Barbosa & Rodrigues 2016), and is might be intermediated by chemical communication (see Rodrigues et al 2019). 6).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This process is quite similar to that observed in other Cyclocephala species such as C. melanocephala, C. testaceipennis, and C. verticalis (Rodrigues et al 2014, Barbosa & Rodrigues 2016. Female selection in Scarabaeidae may be related to the recognition of male sexual maturity as in Canthon cyanellus cyanellus (LeConte, 1859) (Fávila 1988) and C. verticalis (Barbosa & Rodrigues 2016), and is might be intermediated by chemical communication (see Rodrigues et al 2019). 6).…”
Section: Discussionsupporting
confidence: 71%
“…Sensilla placodea was predominant in males and females of this species, while sensilla coeloconica and sensilla basiconica occurred in smaller quantities. Such dominance of sensilla placodea was also found in other Dynastinae species such as Oryctes rhinoceros (Linnaeus, 1758) (Renou et al 1998), and in other phytophagous subfamilies such as Anomala iconstans Burmeister, 1844 (Rutelinae, Rodrigues et al 2019). Larsson et al (2001) studied the antennal sensilla of Anomala cuprea (Hope, 1839) and concluded that the outer sensilla placodea are responsible to detecting sexual pheromones while the inner ones are responsible for detecting plant volatiles.…”
Section: Discussionmentioning
confidence: 65%
“…However, some Scarabaeidae species present higher differences in the amounts of sensilla between males and females. A total of 7428 and 1560 sensilla were quantified in the antennae of males and females of Dasylepida ishigakiensis (Tanaka et al, 2006) respectively, while 7784 sensilla were quantified in females and 5741 in males of Anomala inconstans Burmeister, 1844 (Rodrigues et al, 2019;Rutelinae).…”
Section: Discussionmentioning
confidence: 99%
“…Sensilla present in the antennae of adults of Scarabaeidae are responsible for detecting various stimuli linked to their behavior, such as detection of host plants, sexual pheromone, and oviposition sites, among other functions (e.g., Schneider, 1964;Leal and Mochizuki, 1993;Romero-López et al, 2004, 2010Li et al, 2015;Rodrigues et al, 2019 Studies have been carried out to describe antennal sensilla for some groups of Scarabaeidae pests. Sensilla auricilica, s. basiconica, s. chaetica, s. coeloconica, s. placodea, and s. trichodea have been described in antennae of Anomala Samouelle (1819), Phyllophaga Herris (1827), and Popillia Serville (1825) (Leal and Mochizuki, 1993;Kim and Leal, 2000;Ochieng et al, 2002;Romero-López et al, 2004, 2010Rodrigues et al, 2019). However, there is no information about the antennal sensilla of Liogenys.…”
Section: Introductionmentioning
confidence: 99%
“…During the couple formation, these beetles usually use chemical communication detecting released odors using their antennal sensilla (Meinecke, 1975;Leal, 1998). Sensilla types and number vary with species but also between males and females within a species, especially for Scarabaeidae (Ochieng et al, 2002;Romero-López et al, 2004, 2010Tanaka et al, 2006;Handique et al, 2017;Rodrigues et al, 2019).…”
Section: Introductionmentioning
confidence: 99%